Certification of fitness to drive in sleep apnea patients: Are we doing the right thing?. (1st July 2018) - Grote, Ludger; Svedmyr, Sven; Hedner, Jan
Abstract: New European Union (EU) regulations state that untreated moderate to severe obstructive sleep apnea (OSA) coincident with excessive daytime sleepiness (EDS) constitutes a medical disorder leading to unfitness to drive. However, fitness to drive can be re‐established by successful treatment of OSA and EDS. The aim of the current study was to compare patients undergoing the certification process with those of an unselected OSA patient cohort. The study compared consecutive patients in the certification group ( n  = 132) with a representative group of OSA patients with a current driving license and an Apnea Hypopnea Index (AHI) ≥ 15 n/h ( n  = 790). The adherence to positive airway pressure (PAP) therapy and the change in EDS (Epworth Sleepiness Scale [ESS] score) with treatment were analysed. Patient characteristics and severity of sleep apnea did not differ significantly between groups (certification/reference group: BMI 30 ± 5/31 ± 5 kg/m 2, AHI 33 ± 20/36 ± 20 n/hr, ESS 12 ± 6/11 ± 5). However, the certification group was oversampled with elderly drivers (70–85 years: 22% vs. 9%, p  = 0.001). PAP compliance was higher in the certification group than in the reference group (PAP use ≥ 4 hr/night in 96% vs. 53%, p  = 0.001) and mean ESS reduction was ‐8.0 (‐8.9 – ‐7.1) versus ‐4.0 (‐4.4 – ‐3.5), respectively ( p  < 0.001). Patients attending the fitness to drive evaluation reported almost complete adherence to continuous positive airway pressure (CPAP) and elimination of EDS symptoms. Besides possible baseline differences, this strong response may be explained by factors such as a selection process of elderly patients, a self‐rating component in the assessment of the treatment response and the threat of a driving license suspension. Our data suggest that an improved certification process with objective rather than subjective components, along with a reduced selection bias, is warranted.